Preliminary report on paleomagnetic study of the Yamato Mountains (Massifs B and C), East Antarctica - Ishikawa, Naoto; Funaki, Minoru (National Institute of Polar Research, 1998)
P(論文) Paleomagnetic measurements were performed on granitic gneisses, syenites and granitic dike rocks from Massifs B and C of the Yamato Mountains in East Antarctica. The stable magnetic components carried by magnetite were isolated from granitic gneiss samples from two sites at Massif B and syenite samples from two sites at Massif C. The component directions are well grouped in each massif, but are different between the two massifs. The virtual geomagnetic pole (VGP) position of the gneisses is near the Cambrian, Silurian and upper Devonian segments of the apparent polar wander path (APWP) of East Gondwanaland, while that of the syenites is near the Ordovician segment. These comparisons are not supported by previous K-Ar age data, except the comparison between the gneiss pole and the upper Devonian segment of the APWP. The anisotropy of magnetic susceptibility (AMS) was also measured for samples at the four sites. The gneisses and syenites showed consistent magnetic fabrics within each massif. Especially, the Kl direction of the gneisses is almost parallel to the petrographical foliation. The following possibilities may be considered in order to explain the inconsistency between the VGP positions and the APWP of East Gondwanaland and the difference in the VGP positions between the gneisses and syenites: (1) differential tectonic movement between the two massifs and/or (2) the deviation of remanent acquisition in anisotropic rock or internal deformation in the rock bodies. departmental bulletin paper